Active Fractions from Asparagus racemosus Willd. with Thrombolytic, Membrane Stabilizing and Free Radical Scavenging Activities - Jalil, Md Abdul; Rahman, Mohammad Sharifur; Rahman, SM Ashikur; Rashid, Ridwan B; Rashid, Mohammad A (Bangladesh Pharmaceutical Journal, 2015)
Abstract not available Bangladesh Pharmaceutical Journal 18(2): 183-186, 2015